Metátese de fechamento de anéis de derivados da R-(-)- Carvona - Desiderá, André Luiz (Universidade Federal de São Carlos, 2012)
In this work was developed a new synthetic route to obtain cicloeptenone not conjugated selectively, through a faster and simpler methodology, and in accordance with good practices of green chemistry. By experimental techniques of nuclear magnetic ressonance (NMR) were assigned the stereochemistry of two diastereoisomeric pairs. Intermediate compounds were synthesized for the synthesis of sesquiterpenes guaianes (a), nor-guaianes (b) and pseudo-guaianes (c). To react the mono-allylated to form bis-alilados products with and without replacement, for further formation of compounds containing ring-type spiro[4.6]undecane. It was also developed a new methodology for formation of tensioned spiro rings (d) derivatives from (R)-carvone, using the reaction of ring closure metathesis. Using this methodology allylation, obtained was a precursor for a new way to reach the system bicyclo [5.3.0] decane (e). In total, 18 compounds were synthesized, of which 7 are unpublished.
Keywords: Química orgânica; Cicloeptenona; Sesquiterpenos; Alquilação; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA